Transport phenomena in an annular tube : the effect of viscous dissipation on heat transfer - Aung Mylnt Lwin (2008)
This report investigates the energy transport in an annular tube for forced convection subjected to different wall temperatures. The flow is considered laminar and fully developed, and includes viscous dissipation effect.